2021
DOI: 10.1101/2021.11.12.468411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortical-subcortical structural connections support transcranial magnetic stimulation engagement of the amygdala

Abstract: The amygdala processes valenced stimuli, influences affective states, and exhibits aberrant activity across anxiety disorders, depression, and PTSD. Interventions that modulate amygdala activity hold promise for treating transdiagnostic affective symptoms. We investigated (N=45) whether transcranial magnetic stimulation (TMS) elicits indirect changes in amygdala activity when applied to ventrolateral prefrontal cortex (vlPFC), a region important for affect regulation. Harnessing in-scanner interleaved TMS/func… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 96 publications
(224 reference statements)
0
4
0
Order By: Relevance
“…We envision that these results may contribute to the design of brain stimulation paradigms that—beyond maps of direct connectivity—also leverage knowledge of network communication dynamics [63]. For example, models of polysynaptic transmission could inform the selection of stimulation sites for indirect modulation of deep gray matter structures by non-invasive techniques, such as transcranial magnetic stimulation [64, 65].…”
Section: Discussionmentioning
confidence: 99%
“…We envision that these results may contribute to the design of brain stimulation paradigms that—beyond maps of direct connectivity—also leverage knowledge of network communication dynamics [63]. For example, models of polysynaptic transmission could inform the selection of stimulation sites for indirect modulation of deep gray matter structures by non-invasive techniques, such as transcranial magnetic stimulation [64, 65].…”
Section: Discussionmentioning
confidence: 99%
“…The main mechanism of action proposed for rTMS in SUD treatment is to activate dopamine function in meso-cortico-limbic system and a reinstaining of extracellular glutamate and dopamine concentrations, which could trigger changes of dendritic spine density, neurotransmitter receptor expression, neuronal degeneration, and microglial activation which could explain the microstructural reversive results in basal ganglia and PFC (8,51,52). A previous study has found that rTMS can reach deep subcortical structures such as the amygdala through stimulation of cortical to subcortical connections (53). Our electric-field simulations show that active rTMS in patients with CUD may have reached deep structures reflected by changes in NODDI metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Another human study using multiple sites found that the abnormal intrinsic and extrinsic circuits of the striatum provided a robust neuroimaging biomarker for the diagnosis of schizophrenia 63 . The identified heterogeneous connections between specific brain regions provide potential targets for treatments 64 and neuromodulations 65 . In addition, whole-brain connections allow for graph theory to be used to identify the functional subsystem of the brain and the network properties 66 .…”
Section: Macaque Brainnetome Atlas: Parcellation and Connectionmentioning
confidence: 99%